PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN ASING TERHADAP BIAYA - Risman, Lia; Zuraida, Zuraida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine the effect of managerial ownership, institutional ownership, and foreign ownership on agency costs in non-financial companies listed on the Indonesia Stock Exchange in 2015-2017. The independent variables are managerial ownership, institutional ownership, and foreign ownership. The dependent variable is the agency cost which is proxied as sales and general administration expenses. This study uses secondary data in the form of annual financial reports of non-financial companies listed on the Indonesia Stock Exchange in 2015-2017. The sample in this study consisted of 64 non-financial companies which were taken using a purposive sampling method. Data analysis used multiple linear regression analysis. The results of this study indicate that managerial ownership, institutional ownership and foreign ownership have a significant negative effect on agency costs.